SOCIAL INSURANCE PROGRAMS FOR REDUCING SOCIAL INEQUALITY - Stozhok, Liudmyla (Стратегічна панорама, 2024)
The article emphasizes the importance of studying the insurance aspects of social protection for the population, particularly considering that the preservation and restoration of human capital are key elements in the country's reconstruction initiatives. Drawing from an analysis of various scientific approaches, the author concludes that there is a greater focus on research examining the protection of insured individuals from social risks within the broader context of social protection of the population, as compared to studies specifically centered on social insurance. The author argues that in the context of the uncertainty and unpredictability of war’s consequences, along with the emergence of new labor market participants – such as combatants, veterans, disabled veterans, and caregivers – the assessment of social risks becomes a continuous process. This ongoing assessment is necessary due to the increasing likelihood of individuals shifting between roles within the social insurance system, moving from contributors to dependents. Key factors driving the growing financial incapacity of the social insurance system to meet both qualitative and quantitative demands include the large-scale reduction of the labor force, premature exit from employment, and declining labor productivity. The article elucidates the role of social insurance in safeguarding the working-age population by maintaining their purchasing power in the short term during periods of reduced or lost work capacity, as well as in the long term after the end of employment. The author underscores the importance of social insurance programs in facilitating the exercise of social rights, thereby reducing inequality and social exclusion while protecting individual well-being. It is emphasized that social insurance programs do not offer protection against the diminished opportunities to for investing in human capital, nor do they adequately support future generations. The author argues that compulsory social insurance serves as a reliable mechanism for reducing vulnerability to social risks. Both mandatory and voluntary participation in the social insurance system are effective tools for managing social risks throughout life, as they reinforce individual responsibility in safeguarding against income inequality during periods of instability and limited employment opportunities. The findings demonstrate that the primary role of social insurance in the reconstruction of the country is to provide continuous protection of human capital throughout life, emphasizing inclusion to prevent social burnout and the exacerbation of social inequality and poverty. The purpose of this article is to elucidate the content of social insurance programs within the social insurance system and to underscore their importance in managing emerging social risks, with particular attention to the relationship between program quality and responsiveness to the consequences of war. To fulfill this purpose, the article employs methods of analysis, generalization, and a systematic approach.